An active cognitive lifestyle as a potential neuroprotective factor in Huntington's disease. (January 2019) - Garcia-Gorro, Clara; Garau-Rolandi, Maria; Escrichs, Anira; Rodriguez-Dechicha, Nadia; Vaquer, Irene; Subira, Susana; Calopa, Matilde; Martinez-Horta, Saul; Perez-Perez, Jesus; Kulisevsky, Jaime; Muñoz, Esteban; Santacruz, Pilar; et al.
Abstract: A cognitive stimulating lifestyle has been observed to confer cognitive benefits in multiple neurodegenerative diseases. However, the underlying neurobiological basis of this phenomenon remains unclear. Huntington's disease can provide a suitable model to study the effects and neural mechanisms of cognitive engagement in neurodegeneration. In this study, we investigate the effect of lifestyle factors such as education, occupation and engagement in cognitive activities in Huntington's disease gene carriers on cognitive performance and age of onset as well as the underlying neural changes sustaining these effects, measured by magnetic resonance imaging. Specifically, we analyzed both gray matter volume and the strength of connectivity of the executive control resting-state network. High levels of cognitive engagement were significantly associated with more preserved executive functions, a delay in the appearance of symptoms, reduced volume loss of the left precuneus and the bilateral caudate and a modulation of connectivity strength of anterior cingulate cortex and left angular gyrus with the executive control network. These findings suggest that a cognitively stimulating lifestyle may promote brain maintenance by modulating the executive control resting-state network and conferring protection against neurodegeneration, which results in a delayed onset of symptoms and improved performance in executive functions. Highlights: In Huntington's disease, a cognitively active lifestyle is associated with benefits. These include better cognitive performance and delayed onset of symptoms. These effects could be mediated by less grey matter loss in caudate and precuneus. Reduced functional connectivity was related with a cognitively active lifestyle. Engaging in cognitive activities could potentially provide brain resistance.